Patients' perceptions of faecal calprotectin testing in inflammatory bowel disease: results from a prospective multicentre patient-based survey*. (2nd December 2018) - Kalla, Rahul; Boyapati, Ray; Vatn, Simen; Hijos, Gonzalo; Crooks, Benjamin; Moore, Gregory Thomas; Hall, Veronica; Lipscomb, George; Gomollón, Fernando; Jahnsen, Jørgen; Singh, Salil
Abstract: Introduction: Despite its success, there appears to be practical issues with Faecal Calprotectin (FC) testing in Inflammatory Bowel Diseases (IBD), including sample collection, delivery and processing delays. Patients' perception and barriers to FC testing are yet to be explored in clinical practice. Method: A prospective patient survey was undertaken at IBD units in UK, Europe and Australia. A 9-point patient-based questionnaire was completed in clinic and included demographics, previous FC testing and FC sample difficulty rating score. Predictors of testing difficulty were derived using multivariable logistic regression analysis. Results: A total of 585 patients with IBD completed the survey; 306 males with a median age of 43 years (IQR: 31–54). There were 446 patients (76%) who had prior FC testing experience. Of these, 37% ( n  = 165) rated FC testing difficult; 'sample collection' ( n  = 106; 67%) being the most common reason reported. Multivariable regression analysis identified age <49 years (odds ratio (OR): 2.5, CI:1.6-4.0), disease duration <35 months (OR 1.4, CI:0.9–2.1) and testing location (UK centre: OR 1.9, CI:1.2-3.1) as predictors of a difficult FC rating score. Conclusions: A total of 37% of patients find FC testing challenging, in particular those aged <49 years, disease duration <35 months. Further studies understanding and addressing these practical issues may aid higher FC uptake in clinic.